1999
DOI: 10.1111/j.1469-445x.1999.01734.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ionic Channels by Deoxycholate in Frog and Human Cell Lines

Abstract: summary Humans, after extensive ileal resection, frequently suffer from diarrhoea, which may be due to an increased delivery of deoxycholate (DOC) to the large intestine. In the frog skin the addition of DOC (0·5 mÒ) to the apical side induced the activation of amiloride-sensitive Na¤ channels and an increase in the unidirectional Cl¦ fluxes. Here we used two established cell lines (AÜ and Cacoµ) to study the effect of DOC on ion channels at cell and membrane level using the patch-clamp technique. In AÜ cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Synthetic detergents (Triton X-100 and ␤-octyl glucoside), however, reduce bilayer stiffness and reversibly shift the inactivation to negative potentials. Moreover, Mauricio and Ferreira [35] demonstrated that a bile salt, deoxycholate, activates both anionic and cationic channels in cultured cell lines from the frog kidney (A6) and from human colonic adenocarcinoma (Caco2). PSB has been presumed to have an almost planar conformation [12], which is well known to be the conformation of bile salts.…”
Section: A Results Of the Experiments Using Psb As A Tool To Determinementioning
confidence: 99%
“…Synthetic detergents (Triton X-100 and ␤-octyl glucoside), however, reduce bilayer stiffness and reversibly shift the inactivation to negative potentials. Moreover, Mauricio and Ferreira [35] demonstrated that a bile salt, deoxycholate, activates both anionic and cationic channels in cultured cell lines from the frog kidney (A6) and from human colonic adenocarcinoma (Caco2). PSB has been presumed to have an almost planar conformation [12], which is well known to be the conformation of bile salts.…”
Section: A Results Of the Experiments Using Psb As A Tool To Determinementioning
confidence: 99%